Natural convection for hot materials confined within two entrapped porous trapezoidal cavities - Varol, Yasin (My University, 2012)
Bitişik iki trapez ortamda akış ve ısı transfernin analizi sayısal olarak yapılmıştır. Geometrik oran, iletim oranı ve farklı Rayleigh sayılarında enerji analizi yapılmıştır.

This paper analyzes the detailed heat transfer and fluid flow within two porous trapezoidal cavities involving cold inclined walls and hot horizontal walls. Flow patterns and temperature distribution were obtained by solving numerically the governing equations, using Darcy's law. Results are presented for different values of the governing parameters, such as Darcy-modified Rayleigh number, aspect ratio of two entrapped trapezoidal cavities and thermal conductivity ratio between the middle horizontal wall and fluid medium. Heat transfer rates are estimated in terms of local and mean Nusselt numbers. Local Nusselt numbers with spatial distribution exhibit monotonic trend irrespective of all Rayleigh numbers for the upper trapezoidal whereas wavy distribution of local Nusselt number occur for the lower trapezoidal.
Makale - Bilimsel Dergi Makalesi - Tek Yazarlı
Keywords: Enerji Geri Kazanımı; Bitişik Trapez Ortam; Doğal Taşınım